Organic Matter Production and Distribution of Nutrients in Eucalyptus Hybrid Plantation Ecosystems in Karnataka - Pande, M. C.; Tandon, V. N.; Rawat, R. S. (Indian Forester, 1987)
Studies on biomass and nutrient distribution have been carried out in an age series plantations of Eucalyptus hybrid in Karnataka. The total above-ground biomass ranged from 19 t/ha to 22 t/ha in Kolar Forest Division and 5 t/ha to 16 t/ha in Madhalli Afforestation Centre. The componentwise distribution of nutrients has also been discussed. A substantial amount of nutrients will be drained off as a result of whole tree harvesting. Some advantage could be gained by leaving follage at the site which contains on an average 30 to 40% of macro- nutrients. Debarking at site is also suggested to check the drain of Ca. Total biomass and nutrient accumulation in ground vegetation, which is gradually made available to the trees has also been discussed.